Performing television history. (September 2018) - Bignell, Jonathan
An expanded conception of performance study can disturb current theoretical and historical assumptions about television's medial identity. The article considers how to write histories of the dominant forms and assumptions about performance in British and American television drama and analyses how acting is situated in relation to the multiple meaning-making components of television. A longitudinal, wide-ranging analysis is briefly sketched to show that the concept of performance, from acting to the display of television's mediating capability, can extend to the analysis of how the television medium 'performed' its own identity to shape its distinctiveness in specific historical circumstances.